Evolution of glomerular filtration rate in HIV‐infected, HIV–HBV‐coinfected and HBV‐infected patients receiving tenofovir disoproxil fumarate. Issue 9 (5th March 2013) - Pradat, P.; Le Pogam, M.‐A.; Okon, J.‐B.; Trolliet, P.; Miailhes, P.; Brochier, C.; Maynard, M.; Bailly, F.; Zoulim, F.; Cotte, L.
Summary We aimed to compare the evolution of estimated glomerular filtration rate (eGFR) in HIV‐, HIV–HBV‐ and HBV‐infected patients treated with tenofovir disoproxil fumarate (TDF). Three groups of patients receiving TDF > 12 months were recruited: 194 HIV‐infected patients, 85 HIV–HBV‐coinfected patients and 50 HBV‐infected patients. eGFR was estimated using the Modification of the Diet in Renal Disease (MDRD) equation. Multivariate regression models were constructed to estimate factors associated with eGFR decrease from baseline. A total of 329 patients were studied. Median follow‐up was 2.7 years. Median eGFR decrease was −4.9 (−16.6 to +7.2) mL/min/1.73 m2. After multivariate stepwise regression analysis, age (P = 0.0002), non‐African origin (P < 0.0001), baseline eGFR (P < 0.0001) and TDF duration (P = 0.02) were associated with eGFR decrease in the whole population, while hypertension, diabetes and type of infection were not. Age (P < 0.0001), non‐African origin (P = 0.0004), baseline eGFR (P < 0.0001) and TDF duration (P = 0.007) remained associated with eGFR decline in HIV and HIV–HBV‐infected patients, while other variables including HIV risk factor, CDC stage, CD4 and HIV‐RNA levels were not. Age (P = 0.03), non‐African origin (P = 0.004), baseline eGFR (P < 0.0001) and baseline HBV–DNA > 2000 IU/mL (P = 0.04) were associated with eGFR decline in HBV and HIV–HBV‐infected patients, while other variables including HBV risk factor and fibrosis stage were not. Estimated glomerular filtration rate decline under TDF therapy appears mainly associated with older age, non‐African origin, higher baseline eGFR and longer TDF administration but not with the type of viral infection. Regular follow‐up of renal function, especially tubular function is recommended during TDF therapy.